Effect of infrared belt and hot water bag on labor pain intensity among primiparous: a randomized controlled trial - Fatemeh Dastjerd; Fatemeh Erfanian Arghavanian; Ameneh Sazegarnia; Farideh Akhlaghi; Habibollah Esmaily; Masoumeh Kordi (BMC, 2023)
Abstract Background Labor pain is complex, paradoxical and varied in every parturient woman. Management of labor pain has been a crucial component in maternity care. Heat therapy is one of the proposed method for labor pain relief. Infrared is one of the methods of heat therapy but there is any study in this regard. This study aimed to compare the effect of the infrared belt and hot water bag on the severity of pain in the first stage of labor among primiparous women. Methods In this clinical trial in the first stage of labor, 20-min cycles of heat therapy were conducted at the dilations of 4-5 and 6-7 cm in the intervention group 1 by an infrared belt and in the intervention group 2 by hot water bag, respectively. The control group received routine care. The severity of the pain was measured by the short-form McGill Pain Questionnaire. Results In total, 136 women consented to participate in this clinical trial study. The mean score of pain intensity was significantly lower in the two intervention groups compared to the control group (P < 0.001). The mean pain intensity was significantly lower in the infrared belt group than in the hot water bag group (P < 0.001). Conclusions Based on these findings, heat therapy with an infrared belt reduced the severity of pain in the first stage of labor. The infrared belt could be used and recommended as a safe and effective pain relief in childbirth and maternity care. Trial registration This study was registered in the Iran Clinical Trial Center with the code of IRCT20190805044446N1 .